Analysis of Village Fund Management in Efforts to Improve Community Welfare in Setuta Janapria Village, Central Lombok 2020-2022 - Nurhaliza, Nurhaliza; Hailuddin, Hailuddin; Manan, Abdul; Wahyunadi, Wahyunadi (Eastasouth Institute, 2024)
The allocation of village budget in Setuta Village has not been evenly distributed in each region. Unequal management of village funds causes inequality in development and community welfare. The primary objective of this study was to analyse the impact of village fund management on improving community welfare in Setuta Village, Janapria Sub-district, Central Lombok Regency. This descriptive quantitative research uses primary data collected from 44 households as samples. The results showed that the management of village funds in Setuta Village was not fully in accordance with applicable regulations. The impact of village fund management on community welfare is in the medium category. The positive impact of village fund management can be seen in the education sector, health, health services, and settlement facilities such as the provision of clean water sources for the community. However, the management of village finances has not yet had a significant impact on increasing income, expenses, living conditions, and transportation facilities.